PEMANFAATAN MEDIA SOSIAL FACEBOOK SEBAGAI MEDIA PENINGKATAN KEMAMPUAN MENULIS MAHASISWA - Marham Jupri Hadi (Jurnalistrendi : Jurnal Linguistik, Sastra dan Pendidikan, 2016)
Facebook has been one of the most commonly used social media to communicate with others for a variety of purposes. As it allows people to share their ideas through writing, thus Facebook is very likely to be used to facilitate language learning, in particular to enhance productive skills. The present article discusses suggested steps in employing such a media as one of the alternatives to enhance students’ writing skills. It also suggests how students’ progress in writing can be assessed.li